Muscular hydatidosis about an exceptional form - Bousbaa, Hicham; Zejjari, Hassane; Cherrad, Taoufik (International Journal of Research in Orthopaedics, 2024)
The preferred localizations of human echinococcosis are the liver and the lungs, of which they represent 85% of cases. They generally pose few diagnostic problems, because they are familiar and frequent. The involvement of the soft parts is exceptional, it represents less than 1% of the localizations of human echinococcosis, frequently constituting surprises of anatomical-pathological or radiological examination. We report the rare observation of a hydatid cyst of the adductors of the thigh and discuss the contribution of magnetic resonance imaging (MRI) in this context and the therapeutic modalities. Certainly; it is a rare case but we must think about this diagnosis, especially in subjects from a country with high endemic, and ask for the necessary explorations in order to make the diagnosis in time and avoid therapeutic errors.